Human BBB-on-a-chip reveals barrier disruption, endothelial inflammation, and T cell migration under neuroinflammatory conditions - Nair, Arya Lekshmi; Groenendijk, Linda; Overdevest, Roos; Fowke, Tania M.; Annida, Rumaisha; Mocellin, Orsola; de Vries, Helga E.; Wevers, Nienke R. (Frontiers in Molecular Neuroscience, 2023)
The blood-brain barrier (BBB) is a highly selective barrier that ensures a homeostatic environment for the central nervous system (CNS). BBB dysfunction, inflammation, and immune cell infiltration are hallmarks of many CNS disorders, including multiple sclerosis and stroke. Physiologically relevant human in vitro models of the BBB are essential to improve our understanding of its function in health and disease, identify novel drug targets, and assess potential new therapies. We present a BBB-on-a-chip model comprising human brain microvascular endothelial cells (HBMECs) cultured in a microfluidic platform that allows parallel culture of 40 chips. In each chip, a perfused HBMEC vessel was grown against an extracellular matrix gel in a membrane-free manner. BBBs-on-chips were exposed to varying concentrations of pro-inflammatory cytokines tumor necrosis factor alpha (TNFα) and interleukin-1 beta (IL-1β) to mimic inflammation. The effect of the inflammatory conditions was studied by assessing the BBBs-on-chips’ barrier function, cell morphology, and expression of cell adhesion molecules. Primary human T cells were perfused through the lumen of the BBBs-on-chips to study T cell adhesion, extravasation, and migration. Under inflammatory conditions, the BBBs-on-chips showed decreased trans-endothelial electrical resistance (TEER), increased permeability to sodium fluorescein, and aberrant cell morphology in a concentration-dependent manner. Moreover, we observed increased expression of cell adhesion molecules and concomitant monocyte adhesion. T cells extravasated from the inflamed blood vessels and migrated towards a C-X-C Motif Chemokine Ligand 12 (CXCL12) gradient. T cell adhesion was significantly reduced and a trend towards decreased migration was observed in presence of Natalizumab, an antibody drug that blocks very late antigen-4 (VLA-4) and is used in the treatment of multiple sclerosis. In conclusion, we demonstrate a high-throughput microfluidic model of the human BBB that can be used to model neuroinflammation and assess anti-inflammatory and barrier-restoring interventions to fight neurological disorders.